Identification of factors related to immunotherapy efficacy and prognosis in patients with advanced head and neck squamous cell carcinoma - Xuanli Xu; Rongrong Li; Lin Zhang; Guopei Zhu; Dandan Ren; Lijia Wu; Xiaoli Gong (BMC, 2021)
Abstract Background Immunotherapy is an important treatment in oncology, but only a fraction of patients with head and neck squamous cell carcinoma (HNSCC) benefit from it. Therefore, the aim of this study was to identify predictive biomarkers of immunotherapy response for HNSCC in order to improve treatment outcomes. Methods Survival analyses and comparative efficacy evaluation were performed to investigate prognostic and therapeutic impact factors in patients with advanced HNSCC following immunotherapy, and to examine the effects of factors including gene mutations, tumor mutational burden (TMB), mutant-allele tumor heterogeneity (MATH), and immune cell infiltration on the survival and efficacy. Results Anti-PD-1 treatment led to a prolonged overall survival (OS) in HNSCC patients with gene mutations compared with those without the mutations, while no significant difference in the OS was found between the two groups of patients. And no marked association between the MATH value and OS was detected in HNSCC patients, whereas patients with either high TMB scores in tissues and blood or high immune cell infiltration displayed a significantly longer OS. Further analysis with efficacy as the primary endpoint revealed no significant differences in the tissue TMB, blood TMB, and MATH value between the patients who responded to immunotherapy and those who did not. Moreover, no significant differences in the expression percentages of positive immune cells in tumor, stroma, and total regions were identified between the above two groups of patients. Conclusion HNSCC is characterized by high mutation rate, high mutation burden, and high level of immune cell infiltration, and a subset of HNSCC patients respond to immunotherapy. Here, we showed that high mutation burden and immune cell infiltration may improve the prognosis of HNSCC patients with immunotherapy, while there was no remarkable effect on the efficacy.